2008
DOI: 10.1007/s11664-008-0602-5
|View full text |Cite
|
Sign up to set email alerts
|

Electromigration-Induced Plasticity: Texture Correlation and Implications for Reliability Assessment

Abstract: Plastic behavior has previously been observed in metallic interconnects undergoing high-current-density electromigration (EM) loading. In this study of Cu interconnects, using the synchrotron technique of white-beam x-ray microdiffraction, we have further found preliminary evidence of a texture correlation. In lines with strong (111) textures, the extent of plastic deformation is found to be relatively large compared with that of weaker textures. We suggest that this strong (111) texture may lead to an extra p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…Based on our earlier observations on similar Cu interconnect samples 8,13 such predamaging would result in the microstructures of Cu grains having dislocations lining up along the length of the interconnect lines with a density (q) of up to 10 15 /m 2 . Evidence of such effects on Cu microstructures has been documented on Cu interconnect samples from various manufacturers 8,13 using the synchrotron x-ray microdiffraction technique. Reference 8 is most relevant to our present study as it specifically describes the dislocation density and configuration, as shown in Fig.…”
Section: Methodsmentioning
confidence: 92%
See 4 more Smart Citations
“…Based on our earlier observations on similar Cu interconnect samples 8,13 such predamaging would result in the microstructures of Cu grains having dislocations lining up along the length of the interconnect lines with a density (q) of up to 10 15 /m 2 . Evidence of such effects on Cu microstructures has been documented on Cu interconnect samples from various manufacturers 8,13 using the synchrotron x-ray microdiffraction technique. Reference 8 is most relevant to our present study as it specifically describes the dislocation density and configuration, as shown in Fig.…”
Section: Methodsmentioning
confidence: 92%
“…The Cu lines in Ref. 8 were fabricated by the Submicron Development Center (SDC) when it was still officially part of AMD in 2006, while the Cu lines of our present study were fabricated by SDC as it is currently part of Spansion, Inc. Both of them were fabricated using the same 65-nm technology node of SDC.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations